INFORMED CONSENT AS A THERAPEUTIC AGREEMENT IN HEALTH SERVICES: PERSETUJUAN TINDAKAN KEDOKTERAN SEBAGAI WUJUD PERJANJIAN TERAPEUTIK DALAM UPAYA PELAYANAN KESEHATAN - Agus Gede Sutamaya; Dey Ravena; Chepi Ali Firman Zakaria (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2022)
Informed Consent as a legal implication of the general agreement regulated in Article 1320 BW is the embodiment of a therapeutic agreement which is included in the law of engagement, specifically a legal relationship between a number of legal subjects who bind themselves to do or not do something to another party. Therapeutic agreement is an agreement formed because of the legal relationship between doctor and patient. Legal relationship is the relationship between legal subjects or between legal subjects and legal objects, which are regulated by law. The conditions for the occurrence of a legal relationship are the existence of a legal basis, namely the legal regulations governing the relationship and the existence of legal events, namely events that have consequences regulated by law. Before giving medical treatment to the patient, based on Law no. 36 of 2009 concerning Health, Law no. 29 of 2004 concerning Medical Practice and Menistry of Health No. 585/Menkes/Per/IX/1989 concerning Approval of Medical Action which was later changed to Menistry of Health No. 290/Menkes/Per/III/2008 Regarding Medical Action Approval, doctors must obtain informed consent from their patients for medical treatment, since without that doctors can be legally blamed for their actions. This paper was made to know and understand that the informed consent is a form of therapeutic agreement in the effort of health services.